Comparative analysis of sizing methods of reservoirs used to harvest rainwater - Amorim, Simar Vieira de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Due to increasing concern with the rational use of potable water, efficient alternatives are sought to reduce consumption, such as the use of rain water. In addition of reducing potable water consumption, it can indirectly be used as a non-structural measure of urban drainage. In this system, the sizing of the reservoir is essential to assessing its financial and economic feasibility. The objectives of this article are to present reservoir sizing methods, as well as apply and compare some of the existing methods in a case study. The AT6 building, used as case study, is located in the campus of the University of São Carlos. It has recently built, being used for lectures of the Medicine and Nursing courses. The following sizing methods were analyzed: Rippl’s method (analytical and graphic), method of consideration of the number of consecutive days with no rain (simplified and with statistical analysis), method of analysis of simulation of a reservoir with an assumed capacity, and practical methods (Brazilian, German, British, and Australian).